Efektivitas Penerapan Prinsip-Prinsip Syariah Dalam Penyelesaian Sengketa Ekonomi Syariah di Badan Arbitrase Syariah Nasional (Basyarnas) - Rosidah, Zaidah Nur; Mahfiana, Layyin (TAWAZUN: Journal of Sharia Economic Law, 2020)
This study aims to determine the application of sharia principles in sharia economic dispute resolution in the National Sharia Arbitration Agency (Basyarnas). This study uses a method of socio legal study, how sharia principles are applied in resolving sharia economic disputes so that they can provide justice for both parties. Secondary data collection is carried out through a literature study of primary legal materials and secondary legal material. Some data was requested for confirmation from the National Sharia Arbitration Agency (Basyarnas) in the Yogyakarta region. To obtain answers to the research problems, 3 activities were carried out simultaneously, namely data reduction, data presentation, conclusion drawing / syllogistic verification of deduction. The results of the research and discussion obtained several conclusions, namely first, Islamic principles have not been maximally implemented by Basyarnas, this can be seen from the basis of the consideration of Basyarnas law in its decision. Basyarnas should also correct in terms of the contract, whether it is in accordance with sharia principles or not so that the arising of the dispute is not solely due to the default of the customer but can also be caused by incompatibility with sharia principles. Second, according to Antony Allot's theory of legal effectiveness, the application of sharia principles in sharia economic dispute resolution has not been carried out in accordance with sharia principles, this is due to the lack of clarity in the case in Basyarnas' decision.